Soil sorption and effects on soil microorganisms of thymol and carvacrol monoterpenes from essential oils of aromatic plants - Thiele-Bruhn, Sören; Shikuku, Victor; Dittrich, Felix; Torjir, Doosuur Naomi; Saini, Mitali; Getenga, Zachary (Frontiers in Environmental Science, 2024)
To increase the biodiversity of agricultural systems, aromatic plants appear particularly promising as additional perennial crops in intercropping. They produce essential oils that contain monoterpenes, for example. These compounds have antibiotic properties that make them interesting for commercialisation as medicinal or pesticide products, but also carry the risk of undesirable effects on soil microorganisms and thus on essential soil functions. To investigate this, the monoterpenes thymol and carvacrol and a set of four typical agricultural soils were selected and soil sorption batch tests and soil toxicity tests were carried out to determine dose-response relationships. Sorption followed second order kinetics and was best described at equilibrium by the non-linear BET isotherm that distinguishes between monolayer and multilayer sorption of the non-polar compounds. While the kinetics were very fast with rate constants of 1.66 × 10 -4 and 0.70 × 10 -4 min -1 for thymol and carvacrol, the strength of sorption remained quite low (Kd 1.93 to 3.69), indicating a high mobility and bioavailability of the monoterpenes. In addition, the relation to single soil properties remained low, indicating a multivariate impact of several soil properties. Although thymol and carvacrol are isomeric compounds, they differed in the rate and strength of sorption as well as in the effects on five selected soil microbiological enzyme activities. In particular, carvacrol caused inhibition of enzyme activities, whereas thymol did not produce measurable or relevant effects in all cases. The effect concentrations of 10% and 25% percent inhibition (EC10, EC25) ranged from <1 µg to several grams per gram of soil and hormesis effects were also observed at low concentrations. On the one hand, this indicates only low toxicity; on the other hand, several of the defined effect thresholds can be reached or exceeded by expected environmental concentrations. This may harbour a risk of adverse effects, but may also have a phytosanitary effect, which requires further research.